Cost Price Analysis Using Full Costing and Activity-Based Costing in Sari Gurih Pak Cipto Tofu Production SMEs - Guritno, Laras Pramesti; Zai, Simon Nisja Putra (Indonesia Accounting Research Journal, 2024)
Improper determination of the cost of goods manufactured can impact the setting of product selling prices and overall business profits. This study aims to evaluate how the cost of goods produced is determined using the company’s method, the full costing method, and the activity-based costing method, and to identify which method is the most effective. The research was conducted at UMKM Tahu Sari Gurih Pak Cipto, located in Gemantar Rt 01/Rw 02, Gemantar, Selogiri, Wonogiri. The study employs both full costing and activity-based costing methods, using a descriptive quantitative approach with observation and interviews. Primary data were collected directly from the business owner. The findings indicate that the company’s method resulted in a cost of goods produced of Rp 16,841.67, the full costing method resulted in Rp 17,481.79, and the activity-based costing method resulted in Rp 16,336.11. Among the three methods, activity-based costing proved to be the most effective, as it yielded the lowest cost of goods produced.